2022
DOI: 10.3390/land11020157
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution of Farmers’ Livelihood Strategies since the 1980s on the Loess Plateau, China

Abstract: Understanding the evolution of farmers’ livelihood strategies (FLS) is crucial for maintaining the sustainable development of farmers’ livelihoods, especially on the arid Loess Plateau, China. This study constructed a novel analytical framework for analyzing the evolution of FLS and the critical influencing factors. Changwu County, an apple cultivation region, was selected as a case study. The results suggest that four types of livelihood strategies (crop-planting, apple-planting, work-oriented, and part-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The contributions of this study are primarily reflected in the following three dimensions: First, unlike most previous studies that were only focusing on livelihood capital or livelihood strategies [3,53], we examined different effects of lease-out on rural household livelihood including on livelihood capital and livelihood strategies. The results confirm both hypotheses and previous studies [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions of this study are primarily reflected in the following three dimensions: First, unlike most previous studies that were only focusing on livelihood capital or livelihood strategies [3,53], we examined different effects of lease-out on rural household livelihood including on livelihood capital and livelihood strategies. The results confirm both hypotheses and previous studies [54].…”
Section: Discussionmentioning
confidence: 99%
“…With the acceleration of industrialization and urbanization, China has witnessed the migration of a large amount of surplus rural labor to the cities as well as the increasingly serious phenomenon of the "hollowing out" of the countryside after reform and opening up [1][2][3]. From 1978 to 2019, the number of people employed in agriculture in Jiangxi Province decreased from 9.687 million to 7.008 million.…”
Section: Introductionmentioning
confidence: 99%
“…Livelihood strategies refer to farmers combining and using different forms of livelihood capital to achieve livelihood goals or pursue active livelihood outcomes [15][16] [17]. The adoption of livelihood strategies not only affects the efficient use of livelihood capital but is also the key to livelihood stability outcomes which play an important role in the sustainable and stable operation of all livelihood systems [18] [19].…”
Section: Farmers' Livelihood Strategiesmentioning
confidence: 99%
“…Wamalwa found that some elements of Jatropha farming as an agricultural strategy can improve farmers' livelihoods [23]. Through a study on agricultural development and farmers' livelihoods on the Loess Plateau, Wu et al found that fruit production was one of the important reasons for the differentiation of farmers' livelihood strategies [24]. Global industrialization and urbanization have promoted the development of non-agricultural industries in rural areas in developing countries, which in turn has promoted the development of farmers' livelihoods [25,26].…”
Section: Introductionmentioning
confidence: 99%